Games for health & mHealth apps for police & blue light personnel: A research review. (September 2021) - Marston, Hannah R.; Hadley, Robin; Pike, Graham; Hesketh, Ian
Previous research has reported adverse health outcomes for emergency services personnel (ESP), outcomes that research more broadly has shown can be improved using a gamification and mobile health (mhealth) apps approach. We conducted a review of research on gamification and mhealth apps for ESP that had been published in the last 19 years using 6 major research databases. The results demonstrated that virtually no relevant research has been published, suggesting a significant gap in the evidence base of an approach that could potentially have significant benefits for the health of ESP.